The Help - Stockett, Kathryn (Amy Einhorn Books/G.P. Putnam's Sons, 2009)
Skeeter returns home to Mississippi from college in 1962 and begins to write stories about the African-American women that are found working in white households, which includes Aibileen, who grieves for the loss of her son while caring for her seventeenth white child, and Minny, Aibileen's sassy friend, the hired cook for a secretive woman who is new to town.